(3ZQjH GdbQBf GdcQjes - (3eMeO Hf GdMSf GdeLGMj GdecfGSj,J (B1103 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdMejO GdCYdi Pi Gdef hGdaVd GdcQje Gdehdi Ld Yf GdJLSje hGdJUhjQ heGdg ai GdSdc ef fXjQ s
(3BNQgG (B:s
(3ef JaSjQ ShQI GdENdGU hGdadb hGdfGS , Ke UdGI GdeGdc GdefGf Ydi GdfHi GdWGgQ GdOjGf hBdg hUMHg GdcQGe efi Ydjge CaVd GdSdGe s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3HMhGTjgG TQhM hJYdjbGJs
(3hgj efXheIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B231s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA GdChd (B- (3bSe GdKGfi (B- (3U (B163 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GddZIs